EVALUATION OF CLINICAL EFFECTIVENESS AND TOLERABILITY OF NEWBORNS TO DRY MILK ADAPTED COMPOUND WITH SYNBIOTICAL PROPERTIES - T.V. Belousova; O.L. Bykadorova ("Paediatrician" Publishers LLC, 2009)
The analysis of specific difference and quantitative state of intestinal micro flora in infants, delivered by Caesarian section, depending of nutrition type, was performed. It was shown that in almost healthy term infant, the intestinal micro biocoenosis becomes formed depending on type and character of nutrition. It was proved that synbiotical formula application is effective for the purpose of stimulation and development of bifido- and lacto bacteria, preventing pathological intestine's colonization in infants. Key words: newborns, Caesarian section, nutrition, intestinal micro flora. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(5):80-83)